PEMANFAATAN WEBSITE DALAM UPAYA MENINGKATKAN KEAKTIFAN SISWA DALAM PEMBELAJARAN MATEMATIKA - Erna Puji Astutik; Hanim Faizah; Prayogo Prayogo (LPPM Universitas PGRI Adi Buana Surabaya, 2017)
The purpose of this research is to provide solutions based on the analysis of the situation conducted on two schools, they are SD Islam Wahid Hasyim and MI Ma'arif Kedensari Sidoarjo conducted through: 1) socialization for teachers in the two schools about the use of website in learning mathematics. In this case the website to be used is a website launched by NCTM which can be accessed through http://illuminations.nctm.org; 2) training for teachers in the two schools on website utilization in mathematics learning; and 3) mentoring the teachers from the two schools in using the website in teaching mathematics. This research includes three main stages, they are planning, implementation, and assessment. The results obtained from this research is that most teachers are able to operate computers, use the internet, access NCTM websites, and run interactive media in the website. Teachers are also able to utilize the NCTM website as a media in teaching mathematics. There is an increase in student activity in learning mathematics by using the website in SD Islam Wahid Hasyim and MI Ma'arif Kedensari that is relevant to the teaching and learning activities increased from 70% to 85% and from 69% to 81%. Most students feel happy with the mathematics learning by using the website, students can use the media on the website and understand the material taught through the media, and students do not have difficulty in learning mathematics by using the website. Keywords: mathematics learning, website, student activity